Sociodemographic and economic factors and cardiovascular mortality in South America: An ecological study - Suárez-Moreno, Freddy Omar (2023)
Objective: To describe the sociodemographic and economic characteristics and the frequency of noncommunicable diseases in the countries of South America and to explore their relationship with cardiovascular mortality during 2021. Methods: Cross-sectional ecological study of secondary data analysis from the 15 countries of South America. The independent variables of the model were: population size, age, male sex, life expectancy at birth, literacy, unemployment, Gini index, gross domestic product, gross national income, and prevalence of diabetes, overweight/obesity, sedentary lifestyle, and hypertension. Data from the World Bank, World Health Organization, Pan American Health Organization and Medline, BIREME and Scielo were collected. Results: Guyana is the country with the highest cardiovascular mortality: 443.5 and Chile the one with the lowest mortality: 116.6. For each year of increase in life expectancy at birth, cardiovascular mortality decreases by 20 deaths per 100,000 inhabitants (β= -20.37; 95% CI; (-29.68- -11.06)) p=0.001; Furthermore, for every 1% increase in the unemployment rate, cardiovascular death increased by 8 per 100,000 inhabitants (β=8.78; 95% CI; (1.30-16.26)) p=0.026. Conclusions: There is a strong positive and negative correlation between life expectancy at birth and the unemployment rate with cardiovascular mortality in South America, respectively.